2x -3y = 12;
x + 3y = 6;
__________(+)
3x = 18;
x = 18÷3;
x = 6;
Then, 3y = 6 - 6;
3y = 0;
y = 0÷3;
y = 0;
The answer is 7 i did it on a calculator lol
Answer:24 dollars hope this helped
Step-by-step explanation:
Answer:
x = 1
Step-by-step explanation:
Given that y varies inversely as x then the equation relating them is
y =
← k is the constant of variation
To find k use the condition y = 5 when x = 3
k = yx = 5 × 3 = 15, thus
y =
← equation of variation
When y = 15 then
15 =
( multiply both sides by x )
15x = 15 ( divide both sides by 15 )
x = 1